ALPL-1 Newtonian Ephemeris of the Planetary System Spanning 4000 years - Dybczyński, P. A.; Jopek, Tadeusz (Acta Astronomica, 1986)
Numerical integration of the equations of motion of the Solar System Planets (except Mercury) is described. The continuous ephemeris obtained in result, spanning the time interval from 1918 BC to 2092 AD is presented.
Keywords: Solar System Planets; planety Układu Słonecznego